A comparison of salmonella serotypes found in the faeces of gulls feeding at a sewage works with serotypes present in the sewage. - Fenlon, D. R. (Cambridge University Press, 1983)
The numbers of salmonella serotypes in raw sewage, sewage sludge and final effluent at a sewage treatment works were determined. Resting gulls which had previously been feeding on the sewage were disturbed and individual faecal samples tested for the presence of salmonellae. The serotypes were compared with those in the sewage. Six serotypes were isolated from the sewage, Salmonella stanley being found in all types of samples. Eleven of the twenty gull faeces samples were positive for salmonellae, a carriage rate of 55%. Seven serotypes were found, S. stanley being most frequent. Three serotypes were found in both sewage and gull faeces.